Kompetensi Komunikasi Pendamping Dan Kepuasan Petani Dalam Pelaksanaan Program Simantri (Communication Competence of Facilitator and Farmer Satisfaction on Simantri Programme) - Kadek Diah Pradnyani; Djuara P Lubis; Eko Sri Mulyani (Institut Pertanian Bogor, 2016)
This study aims to (1) describe communication competence of facilitator on Simantri programme, (2) describe the level of farmer satisfaction toward facilitator, (3) analyze the relationship of internal and external factors offacilitator with their communication competence, and (4) analyze the relationship of facilitator communication competence with farmer satisfaction. It was a survey study and the unit of analysis was the outsourcing facilitator ofSimantri programme. The respondents were 30 facilitators and 150 farmers of Simantri in Klungkung and Jembrana Regency. The methods of collecting data were questionnaire and interview. The data analyzing technique useddescriptive analyzing, Rank Spearman, and Mann-Whitney assisted by SPSS 22.0. The result indicated (1) the level of communication competence of facilitators in Klungkung and Jembrana are generally high (based on self-report and receiver-report); (2) the level of farmers satisfaction are high; (3) internal factor of facilitator has significant correlations with their communication competence and external factor of facilitator (the number of training) hassignificant correlations with their communication competence; (4) almost all indicators on facilitator communication competence has significant correlations with farmer satisfaction. Keywords: communication competence, farmer satisfaction, Simantri programme